Traditional Tolak Bala Ceremony in Tanah Bara Village, Aceh Singkil from an Islamic Law Perspective - Efia, Cut; Tanjung, Dhiauddin; Matsum, Hasan (GoAcademica Research & Publishing, 2024)
Long before Islam came, local culture and beliefs of Animism and Dynamism were very close to the community. It was from here that the belief that disaster would occur because of something or a matter came into existence. Tolak bala in the big Indonesian dictionary is defined as an action to reject disaster; an effort to avoid danger; a series of activities carried out by a group of people to hold a kenduri tolak bala. Everyone certainly longs for safety and happiness, so that if a disaster threatens them, they try to ward it off. Islamic law has stipulated that only Allah is the source of salvation, a Muslim must believe that only Allah controls all good and harm, both those that have not yet befallen and those that have befallen. As in surah az-zumar verse 38; in other letters such as surah al-Baqarah verse 45 also emphasizes human dependence on Allah. This research was conducted in Tanah Bara village, Gunung Meriah District, Aceh Singkil Regency using a descriptive analysis method. The practice of tolak bala in Tanah Bara village on every Wednesday at the end of the month of Syafar. Various series are carried out such as, hajat prayer, dhikr and prayer to ward off disaster, bathing to ward off disaster using KASE and smearing betel water on the forehead of family members. There is no practice of ward off disaster in Tanah Bara Village that performs offerings such as throwing food into the river for offerings. The practice of ward off disaster as has been briefly described, is carried out only as an effort to keep away from danger. The practice of ward off disaster in Tanah Bara Village is legitimated by Islamic law, because it still reflects the spirit of Islamic law, meaning that it is permitted in Islamic law for the practice of ward off disaster in Tanah Bara Village. In the practice of ward off disaster that is carried out, there are no acts of idolatry committed, such as throwing offerings into the river, or throwing food with the aim of offerings. Only the essence of the practice of ward off disaster after using KASE, then diving by realizing it like the flow of water with the KASE, then all diseases disappear. This is the point of the problem of the practice of warding off disaster that the author wants to examine further to obtain legal legitimacy, whether it is permissible or not.